Towards effective regulation of offshore oil and gas waste management in Nigeria - Ofuani, Anwuli Irene (Institute of Marine and Environmental Law, 2014)
The development of the offshore oil and gas industry has been going on for many decades with little thought of the consequences of its activities on the environment. However, in recent years, there has been a clamour by the international community to protect the marine environment from further degradation. Many global, regional and national laws have been made to that effect and some of these laws deal with the offshore oil and gas industry. One area that seems to be deficient in these laws is the management of wastes generated from operational activities of the offshore oil and gas industry especially during exploration and production. This is clearly illustrated by the inadequate regulation of offshore exploration and production (E&P) waste management in Nigeria